2012
DOI: 10.1259/bjr/12938443
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of paediatric haemophilic pseudotumour of the maxillary bone: report of three cases and review of the literature

Abstract: Objectives: Haemophilic pseudotumour (HP) is an extremely rare lesion. The purpose of this study was to describe the CT and MRI features of maxillary bone HPs and introduce the key points to differentiate HP from the mimicking entities in the region. Methods: We retrospectively reviewed three paediatric patients with histologyproven HPs arising from the maxillary bone. All three patients underwent CT and/or MRI. Combined with six previously reported cases in the literature, the imaging features were comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Intra muscular pseudotumours may be seen in areas of greater mobility and more prone to minor trauma such as the major flexors of the limbs, the calf, and forearm flexors. Our review of literature suggested that pseudotumours of the mandible or maxilla, occurred in young patients rather than in adults [2,3,[7][8][9][10]. It has only been described in the dentate region of the mandible and not elsewhere.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Intra muscular pseudotumours may be seen in areas of greater mobility and more prone to minor trauma such as the major flexors of the limbs, the calf, and forearm flexors. Our review of literature suggested that pseudotumours of the mandible or maxilla, occurred in young patients rather than in adults [2,3,[7][8][9][10]. It has only been described in the dentate region of the mandible and not elsewhere.…”
Section: Discussionmentioning
confidence: 83%
“…The possible reasons for pseudotumours arising in the mandible are not clear. Though trauma has been established to be an important etiological factor, sometimes these may occur in the absence of a history of trauma [8]. Tooth eruption is known to cause bleeding [11]; we postulate that the physiologic process of tooth eruption of either the premolar or the second molar itself may have been the cause for pseudotumour developing in the mandible in this case.…”
Section: Discussionmentioning
confidence: 90%
“…In this report, we briefly summarized our case and the previous 24 studies, 1,[3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] which included 32 cases, on haemophilic pseudotumours of the jaw. Table 1 shows the summary of studies conducted between 1968 and 2014, including the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts have been made to treat a haemophilic pseudotumour of the jaw by using treatment modalities such as radiotherapy, 5,10,20,21 cryoprecipitation, 11 curettage, 3,12,17,26 enucleation, 14,23 replacement therapy, 1,3,4,9,15,19,22,25,26 immobilization, 19 ethanol embolization 24 and resection. 4,13 The treatment plan is chosen on a case-by-case basis, and most physicians have accepted that replacement therapy that provides the coagulation factor is a fundamental component of treatment and another appropriate therapy with replacement therapy is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence is in the adult population. There are only a few cases found in the paediatric population [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%